2022
DOI: 10.47441/jkp.v17i2.284
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pelaksanaan Kebijakan Penyederhanaan Birokrasi Di Lingkup Pemerintah Provinsi Kalimantan Selatan

Abstract: To realize effective governance, the central government has issued a policy to simplify the bureaucracy. One of these policies is implemented by equalizing Administrative Positions (JA) to Functional Positions (JF). The Provincial Government of South Kalimantan has followed the mechanism for equalizing JA to JF following the provisions of the applicable laws. However, in its implementation, it is still partially done. The equalization of JA to JF has been carried out by four agencies, namely Bappeda, Balitbang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 5 publications
3
16
0
Order By: Relevance
“…The main tasks & functions, benefits, facilities, and disposition hierarchy are still the same as the old organisation. This is in line with research by Nisa, et al (2022) that the implementation of bureaucratic simplification in local governments has not been in accordance with the work system. The changed position map has no impact on employee performance and motivation.…”
Section: The Impact Of Bureaucratic Simplification On the Performance...supporting
confidence: 91%
See 2 more Smart Citations
“…The main tasks & functions, benefits, facilities, and disposition hierarchy are still the same as the old organisation. This is in line with research by Nisa, et al (2022) that the implementation of bureaucratic simplification in local governments has not been in accordance with the work system. The changed position map has no impact on employee performance and motivation.…”
Section: The Impact Of Bureaucratic Simplification On the Performance...supporting
confidence: 91%
“…This is indicated by the provision of motivation, protection, and the head of the work unit who takes the role of being a place to complain for new functional officials. This is in line with research by Nisa, et al (2022) that the head of the work unit should be able to proactively motivate and internalize employees so that the bureaucratic simplification policy can be implemented more quickly. The things done by the head of the work unit also show that the leader as an authoritarian figure in the organization is expected to provide protection and take on the role of "father" for his subordinates.…”
Section: How Leaders Manage Human Resources After Bureaucratic Simpli...supporting
confidence: 84%
See 1 more Smart Citation
“…According to Handoko (Tsauri, 2013), work career is defined as all jobs or positions handled or held during one's work life, while according to Greenhaus in (Marnis &;Priyono, 2008), career is defined as a pattern of work-related experiences that extend (Marthalina, 2021;Setiawan et al, 2022;Nisa et al, 2022) found that the application of equitable distribution of structural positions to functional positions does not have a direct impact on the career development of apparatuses, while competence and career development have a positive influence on performance (Garaika, 2020;Suhardiman, 2019) in addition, adaptation to work culture affects career development (Alim D.…”
Section: Career Development Of Civil Servantsmentioning
confidence: 99%
“…The problems of the communication dimension, which has not worked optimally, so that it affects other dimensions of policy implementation. 2023) There are inconsistencies in the regulations governing the equalization policy, which means that simplification of competencies and age limits for equalized officials has the potential to impede their career progression, this was also noted in (Tuasamu et al, 2022) that the majority of administrators transferred to functional positions did not meet the educational and competency requirements of the functional positions they would occupy, as well as research (Nisa et al, 2022) that revealed a mismatch between educational qualifications and the requirements of the functional position they would occupy, this is also found in the research (Wahyuningsih et al, 2021) which states that there are still civil servants who occupy functional positions that are not in accordance with their educational background and competencies, as well as in the research (D. H. Pratama et al, 2023) related to job competence, if strict selection and competency tests are conducted, many supervisory and administrative civil servants will not qualify for functional positions. In addition to competency, issues were identified within the work system that had not been addressed by the Lubuklinggau City Government after position equalization.…”
Section: Minister Of Administrative Reform and Bureaucratic Reform Wi...mentioning
confidence: 99%